Vanuatu : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper describes economic developments in Vanuatu during the first half of the 1990s. In 1995, economic growth recovered to more than 3 percent, following the slowdown in the previous year, owing to increased agricultural production, especially of copra and cocoa, and the growth in construction and tourism. Inflation remained below 2 percent, notwithstanding the impact of a new turnover tax on consumer prices, owing to a sharp reduction in import tariffs and a decline in rental prices. The overall fiscal deficit narrowed mainly owing to lower capital expenditure.